2023
DOI: 10.1080/10646175.2023.2169086
|View full text |Cite
|
Sign up to set email alerts
|

“Dream Now, Travel Tomorrow”: Communicating the Nation Branding of Indonesia through Tourism-Based Social Media

Abstract: The Ho ard Journal of Communications publishes on ethnic and cultural communication, gender and ethnic representations in the media and interracial issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…The incorporation of mobile devices and social networking sites has become an indispensable component of individuals' everyday routines, facilitating communication with peers, and offering easy access to information. An investigation into the application of social media among Indonesian youth revealed that the most utilized platforms are Facebook, Twitter, and Instagram (Murti et al, 2023;Wibowo & Hartono, 2023). The findings of the investigation divulged that the employment of social media by young individuals is not purely for recreational purposes but rather, encompasses utilization for retrieval of information, interaction, and exchange of data.…”
Section: Current Lifestyle Of Indonesia's Multicultural Youthmentioning
confidence: 99%
“…The incorporation of mobile devices and social networking sites has become an indispensable component of individuals' everyday routines, facilitating communication with peers, and offering easy access to information. An investigation into the application of social media among Indonesian youth revealed that the most utilized platforms are Facebook, Twitter, and Instagram (Murti et al, 2023;Wibowo & Hartono, 2023). The findings of the investigation divulged that the employment of social media by young individuals is not purely for recreational purposes but rather, encompasses utilization for retrieval of information, interaction, and exchange of data.…”
Section: Current Lifestyle Of Indonesia's Multicultural Youthmentioning
confidence: 99%